CYBER SEXUAL HARASSMENT & VICTIM PROTECTION LAWS: A COMPARATIVE STUDY OF MALAYSIA, SINGAPORE, AND AUSTRALIA - PAVITRA KALAISELVAN,; HAEZREENA BEGUM BINTI ABDUL HAMID,; JAL ZABDI BIN MOHD YUSOF, (Journal of Malaysian and Comparative Law, 2025)
Sexual harassment is a widespread phenomenon, affecting various people across the globe, irrespective of gender and age. With the technological revolution, sexual harassment has infected the digital realm in the form of cyber sexual harassment, where an individual can be sexually harassed without the physical presence of the harasser. As cyberspace is a global platform for communication, the harasser could harass his target from any part of the world while remaining anonymous. On the other end, the victim could suffer in the real world with harm such as emotional disturbances and mental health issues. Thus, this paper aims to address the gap in Malaysian laws to protect victims of cyber sexual harassment. To achieve this aim, the sexual harassment laws in Malaysia and their weaknesses will be examined. Following this, a comparative study will be conducted on laws relating to cyber sexual harassment in Singapore and Australia.